2022
DOI: 10.3389/fnagi.2022.955735
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic potential of pomegranate in age-related neurological disorders

Abstract: Age-related neurological disorders [AND] include neurodegenerative diseases [NDDs] such as Alzheimer's disease [AD] and Parkinson's disease [PD], which are the most prevalent types of dementia in the elderly. It also includes other illnesses such as migraine and epilepsy. ANDs are multifactorial, but aging is their major risk factor. The most frequent and vital pathological features of AND are oxidative stress, inflammation, and accumulation of misfolded proteins. As AND brain damage is a significant public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 261 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that polyphenols and other compounds in pomegranate and its bioactive waste have neuroprotective effects, as has been demonstrated by several studies. Pomegranate peel owes its neuroprotective effect majorly to proanthocyanidin compounds, ellagitannins, punicalagin, granatin, flavonoids, and phenolics compounds (Emami Kazemabad et al., 2022 ). In a neuronal environment, polyphenols extracted from pomegranate peel improve brain neurochemistry through their ability to inhibit NF‐κB actions, which is responsible for mRNA transcription of toxic and proinflammatory biomolecules.…”
Section: Health Benefitsmentioning
confidence: 99%
“…It is worth mentioning that polyphenols and other compounds in pomegranate and its bioactive waste have neuroprotective effects, as has been demonstrated by several studies. Pomegranate peel owes its neuroprotective effect majorly to proanthocyanidin compounds, ellagitannins, punicalagin, granatin, flavonoids, and phenolics compounds (Emami Kazemabad et al., 2022 ). In a neuronal environment, polyphenols extracted from pomegranate peel improve brain neurochemistry through their ability to inhibit NF‐κB actions, which is responsible for mRNA transcription of toxic and proinflammatory biomolecules.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Experimental evidence suggests that feeding disorders, like malnutrition and obesity, have an impact on AD [ 72 , 73 , 74 ], whereas a diet based on foods rich in vitamins and polyphenols seems to be able to prevent and reduce the AD onset [ 75 ]. Regarding the human studies, more data needs to be collected in order to better understand the positive relationship between polyphenol and AD [ 76 ], while several animal model studies support this hypothesis.…”
Section: Pomegranate Fruit (Pf)mentioning
confidence: 99%
“…Pomegranate is usually consumed as whole fruit, juice, or botanical dietary e In recent years, pomegranate has become popular for its numerous benefits rel human health; thus, numerous different pomegranate-based products appeared market such as powdered capsules and tablets, tea, jam, wine, jelly, and spices [71 Experimental evidence suggests that feeding disorders, like malnutritio obesity, have an impact on AD [72][73][74], whereas a diet based on foods rich in vitami polyphenols seems to be able to prevent and reduce the AD onset [75]. Regarding the studies, more data needs to be collected in order to better understand the p relationship between polyphenol and AD [76], while several animal model studies s this hypothesis.…”
Section: Pomegranate Juice and Extracts Against Admentioning
confidence: 99%
“…This beneficial effect is likely due to the abundance of bioactive compounds in pomegranate peel, including polyphenols, anthocyanidins, tannic acid, gallic acid, and ellagic acid. These compounds have been shown to possess antioxidant properties, which can help protect against OS, a factor associated with depression and anxiety (Kazemabad et al, 2022 ). Additionally, animal studies have shown that pomegranate peel extract improves depressive behaviors brought on by ongoing stress (Naveen et al, 2013 ).…”
Section: Clinical Studies On the Therapeutic Effects Of Pomegranate (...mentioning
confidence: 99%